Active disturbance rejection synchronization control for parallel electro-coating conveyor. (June 2020) - Yao, Suhua; Gao, Guoqin; Gao, Zhiqiang; Li, Shuai
Abstract: A bandwidth-parameterized active disturbance rejection synchronization control (ADRSC) is proposed for the parallel electro-coating conveyor. The Laplacian matrix is extracted from the newly defined adjacent-cross-coupling errors and embedded in the controller. It is shown that the proposed ADRSC possesses the capability to achieve synchronization by reformulating cross-coupling as average disturbance to be rejected, thus reducing the dynamics to the canonical form of chained integrators. Furthermore, the upper bound of the bandwidth is established as the trade-off between the accuracy of synchronization and stability. The main contribution of this paper is to extend the active disturbance rejection principle to the accommodation of cross-coupling in synchronization. Simulations and experiments show that this proposed method is effective and practical. Highlights: Laplacian matrix from newly defined coupling errors. Proposal of ADRSC for synchronization in Laplacian-matrix-embedding way. Trade-off at the upper bound of bandwidth parameter.